ON THE DYNAMIC VERTICAL WHEEL-RAIL FORCES AT LOW FREQUENCIES - Mădălina DUMITRIU (Fiabilitate şi Durabilitate)
To homologate the railay vehicles, from the pespective of dynamic behavior, the dynamic forces generated at the wheel/rail interface should be limited, in order to comply with the criterion regarding the rolling track fatigue. The meeting of this requirement implies the vehicle adjustment in its construction. This paper examines the influence of certain vehicle parameters upon the magnitude of the dynamic vertical loads derived during travelling on a track with random irregularities. It will be shown how the minimizing condition of the dynamic vertical loads can result into the best primary suspension damping